2021
DOI: 10.1126/sciadv.abj2610
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in cognitive disability after a major disaster: A natural experiment study

Abstract: Cognitive disability following traumatic experiences of disaster has been documented; however, little is known about heterogeneity in the association across individuals. In this natural experiment study of approximately 3000 Japanese older adults in an area directly affected by the 2011 Great East Japan Earthquake, the baseline survey was established 7 months before the 2011 earthquake. To inductively identify heterogeneity in postdisaster cognitive disability by predisaster characteristics, we applied a machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…The global community has committed to ambitious targets articulated in the Sustainable Development Goals (Burke et al, 2021;Daoud et al, 2016;Halleröd et al, 2013). Although many governments globally are vigilant in implementing public policies to improve human development for their populations (Conklin et al, 2018;Coutts et al, 2019;Ponce et al, 2017;Shiba et al, 2021), policymakers lack reliable methods to monitor the effects of their policies at a sufficiently granular level over time and space (Daoud, 2015). To tackle this lack, scholars are creating innovative methods that capitalizes on the predictive accuracy of ML and the visual granularity supplied by EO (Burke et al, 2021;Daoud and Dubhashi, 2020;Rolf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The global community has committed to ambitious targets articulated in the Sustainable Development Goals (Burke et al, 2021;Daoud et al, 2016;Halleröd et al, 2013). Although many governments globally are vigilant in implementing public policies to improve human development for their populations (Conklin et al, 2018;Coutts et al, 2019;Ponce et al, 2017;Shiba et al, 2021), policymakers lack reliable methods to monitor the effects of their policies at a sufficiently granular level over time and space (Daoud, 2015). To tackle this lack, scholars are creating innovative methods that capitalizes on the predictive accuracy of ML and the visual granularity supplied by EO (Burke et al, 2021;Daoud and Dubhashi, 2020;Rolf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, accelerated cognitive decline was also observed in a recent study in individuals who lost their home during the 2011 earthquake in Japan [ 208 ]. Even though there was quite some heterogeneity between individuals, the individuals that seemed most vulnerable to post-disaster accelerated cognitive decline tended to be less educated, as well as older, unmarried, not working, living alone, and had also baseline health problems [ 208 ].…”
Section: Potential Mechanisms Underlying Ndanmentioning
confidence: 98%
“…Additionally, another recently published study, which did not specifically look at IQ, but that investigated person-specific cognitive trajectories, also found that terminal decline contributes on average for about 70% to late-life cognitive loss in the investigated cohort [ 207 ]. Interestingly, accelerated cognitive decline was also observed in a recent study in individuals who lost their home during the 2011 earthquake in Japan [ 208 ]. Even though there was quite some heterogeneity between individuals, the individuals that seemed most vulnerable to post-disaster accelerated cognitive decline tended to be less educated, as well as older, unmarried, not working, living alone, and had also baseline health problems [ 208 ].…”
Section: Potential Mechanisms Underlying Ndanmentioning
confidence: 99%
“…Learning algorithms, however, do not require such explicit programing. They estimate many different models-possibly thousands-using random cuts of the data, and thus suggest where impact heterogeneity is largest (Shiba et al 2021). They produce such suggestions by providing a list of variables that were important in building these many different models.…”
Section: Expected Individual Counterfactualsmentioning
confidence: 99%